ANALISIS KESULITAN MEMBACA SISWA DENGAN MODEL TEMATIK FRAGMENTED PADA PEMBELAJARAN BAHASA INDONESIA DI SDN 32 CAKRANEGARA - Yani, Haetul; Ermiana, Ida; Jayadi, Hilwan; Rahayu , Winda Tri (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
This study aims to describe the factors causing reading difficulties among fourth-grade students at SDN 32 Cakranegara and identify effective intervention strategies to address them. A descriptive qualitative approach was employed, with data collected through participatory observation, in-depth interviews, reading tests, and documentation. The findings revealed that reading difficulties were influenced by a lack of phonological awareness, limited family support, and suboptimal teaching methods. To overcome these challenges, interventions such as the phonics method, multisensory learning, educational technology, and active involvement of teachers and parents were implemented. These strategies were applied within the fragmented thematic learning model, which allows a focused approach to reading skills within the Indonesian language subject. The results highlight the importance of an integrated and collaborative approach in improving reading abilities among elementary students with literacy difficulties. This research is expected to serve as a reference for planning instruction and early intervention in creating an inclusive literacy environment.